Impact of worsening of aortic insufficiency during HeartMate 3 LVAD support. Issue 3 (23rd October 2020) - Imamura, Teruhiko; Narang, Nikhil; Kim, Gene; Nitta, Daisuke; Fujino, Takeo; Nguyen, Ann; Grinstein, Jonathan; Rodgers, Daniel; Ota, Takeyoshi; Raikhelkar, Jayant; Jeevanandam, Valluvan; Sayer, Gabriel; et al.
Abstract: Aortic insufficiency remains a difficult to treat and highly morbid condition even in the era of HeartMate 3 left ventricular assist devices (LVADs). The prognostic nature of the longitudinal progression of aortic insufficiency, however, remains unknown. We prospectively collected data on patients who received HeartMate 3 LVAD implantation, who had assessments of aortic insufficiency using a novel Doppler echocardiography obtained at outflow graft at three (baseline) and 6 months postimplant. Patients with moderate or greater aortic insufficiency at baseline were excluded. The risk of aortic insufficiency progression on 1‐year death and readmission for heart failure was investigated. In total, 41 patients (median 51 years old and 29 males) were included. All patients had less than moderate aortic insufficiency at baseline. Of them, 22 patients had worsening aortic insufficiency for 3 months following baseline assessments, which was associated with a significantly higher risk of 1‐year death or heart failure readmission rate (41% vs. 11%, P = .023) with a hazard ratio of 3.24 (95% confidence interval 1.02‐18.5, P = .038) adjusted for device speed at baseline and destination therapy indication. In patients with HeartMate 3 LVADs, progressive aortic insufficiency may be associated with a higher risk of 1‐year death or readmission for heart failure. Close monitoring of patients with baseline aortic insufficiency should be considered as a measure to risk‐stratify those for future adverse events.